Pre-exposure to Lower-Level Noise Mitigates Cochlear Synaptic Loss Induced by High-Level Noise - Fan, Liqiang; Zhang, Zhen; Wang, Hui; Li, Chunyan; Xing, Yazhi; Yin, Shankai; Chen, Zhengnong; Wang, Jian (Frontiers in Systems Neuroscience, 2020)
The auditory sensory organs appear to be less damaged by exposure to high-level noise that is presented after exposure to non-traumatizing low-level noise. This phenomenon is known as the toughening or conditioning effect. Functionally, it is manifested by a reduced threshold shift, and morphologically by a reduced hair cell loss. However, it remains unclear whether prior exposure to toughening noise can mitigate the synaptic loss induced by exposure to damaging noise. Since the cochlear afferent synapse between the inner hair cells and primary auditory neurons has been identified as a novel site involved in noise-induced cochlear damage, we were interested in assessing whether this synapse can be toughened. In the present study, synaptic loss was induced by a damaging noise exposure (106 dB SPL) and compared across Guinea pigs who had and had not been previously exposed to a toughening noise (85 dB SPL). Results revealed that the toughening noise heavily reduced the synaptic loss observed 1 day after exposure to the damaging noise. Although it was significant, the protective effect of the toughening noise on permanent synaptic loss was much smaller. Compared with cases in control group without noise exposure, coding deficits were seen in both toughened groups, as reflected in the compound action potential by signals with amplitude modulation. In general, the pre-exposure to the toughening noise resulted in a significantly reduced synaptic loss by the high-level noise. However, this morphological protection was not accompanied by a robust functional benefit.